Clinical networking results in continuous improvement of the outcome of patients with acute promyelocytic leukemia - Koury, LCDA (2024)
The introduction of all-trans retinoic acid combined with anthracyclines has significantly improved the outcomes for patients diagnosed with acute promyelocytic leukemia (APL), and this strategy remains the standard of care in countries in which arsenic trioxide is not affordable. However, data from national registries and real-world databases indicate that low- and middle-income countries (LMIC) still face disappointing results, mainly because of high induction mortality and suboptimal management of complications. The American Society of Hematology established the International Consortium on Acute Leukemias (ICAL) to address this challenge through international clinical networking. Here, we present the findings from the International Consortium on Acute Promyelocytic Leukemia study involving 806 patients with APL recruited from 2005 to 2020 in Brazil, Chile, Paraguay, Peru, and Uruguay. The induction mortality rate has notably decreased to 14.6% compared with the pre-ICAL rate of 32%. Multivariable logistic regression analysis revealed as factors associated with induction death: age of ≥40 years, Eastern Cooperative Oncology Group performance status score of 3, high-risk status based on the Programa Español de Tratamiento en Hematologia/Gruppo Italiano Malattie EMatologiche dell'Adulto classification, albumin level of ≤3.5 g/dL, bcr3 PML/RARA isoform, the interval between presenting symptoms to diagnosis exceeding 48 hours, and the occurrence of central nervous system and pulmonary bleeding. With a median follow-up of 53 months, the estimated 4-year overall survival rate is 81%, the 4-year disease-free survival rate is 80%, and the 4-year cumulative incidence of relapse rate is 15%. These results parallel those observed in studies conducted in high-income countries, highlighting the long-term effectiveness of developing clinical networks to improve clinical care and infrastructure in LMIC.